2016
DOI: 10.1007/s00737-016-0649-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple domains of stress predict postpartum depressive symptoms in low-income Mexican American women: the moderating effect of social support

Abstract: Purpose Prenatal stress can have a lasting effect on women’s mental health after childbirth. The negative effects may be particularly salient in women from low income and ethnic minority backgrounds, who are at increased risk for postpartum depression. However, social support may have the potential to attenuate the negative impact of stress. Methods The present study evaluated 269 Mexican American women (ages 18–42; 83% Spanish-speaking; median income $10,000–$15,000) for prenatal stress (daily hassles, fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 58 publications
3
33
0
1
Order By: Relevance
“…There are indications for the effectiveness of such interventions, for example, a randomized controlled trial investigating the effectiveness of a mindfulness-based stress reduction intervention among individuals diagnosed with Generalized Anxiety Disorder, has shown that such an intervention improved stress reactivity and coping measured in a laboratory stress challenge [55]. Furthermore, research among low-income Mexican American women showed that social support buffered the negative effect of stress on mental health, specifically postpartum depression [56]. Thus, it is worthwhile to design interventions that target not only coping, but also incorporate an element of social support to reduce the negative impact of stress on health.…”
Section: Practical Implications Resulting From This Studymentioning
confidence: 99%
“…There are indications for the effectiveness of such interventions, for example, a randomized controlled trial investigating the effectiveness of a mindfulness-based stress reduction intervention among individuals diagnosed with Generalized Anxiety Disorder, has shown that such an intervention improved stress reactivity and coping measured in a laboratory stress challenge [55]. Furthermore, research among low-income Mexican American women showed that social support buffered the negative effect of stress on mental health, specifically postpartum depression [56]. Thus, it is worthwhile to design interventions that target not only coping, but also incorporate an element of social support to reduce the negative impact of stress on health.…”
Section: Practical Implications Resulting From This Studymentioning
confidence: 99%
“…Nonetheless, information is limited regarding the effects of social support on racial/ethnic minority women in the US, who are at high-risk for experiencing socioeconomic disadvantage and stressful life events. In a cohort of Mexican-American women, moderate to high levels of social support attenuated risk for PPD (Coburn et al 2016), and partner support protected against the negative effect of prenatal stress on infant cortisol reactivity (Luecken et al 2013). For Black mothers, supportive relationships with the father of the baby and the mother's parent were related to lower levels of depressive symptoms (Edwards et al 2012;Westdahl et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…In summary, research on social support and PPD in racial/ethnic minority women in the US is largely limited by relatively small sample sizes and lack of comparison analysis between minority groups with and without PPD (Coburn et al 2016;Gray et al 2000;Martinez-Schallmoser et al 2003;Ugarriza 2006). We address this fundamental gap in knowledge of the relationship between social support and PPD in a large and diverse cross-sectional cohort study of PPD cases and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Social support has long been established as a buffer to maternal perinatal depression 55 , 56 and anxiety 57 and as protecting children from the influence of postnatal depression 55 , 58 , 59 and anxiety 57 . Low social support is associated with prenatal anxiety 60 and partner support is associated with a lower risk of co-morbid postnatal anxiety and depression 61 .…”
Section: Introductionmentioning
confidence: 99%
“…Low social support is associated with prenatal anxiety 60 and partner support is associated with a lower risk of co-morbid postnatal anxiety and depression 61 . In contrast, low-income has also been implicated in postpartum depressive symptoms 56 and difficulties with finances and non-white ethnicity have been implicated in co-morbid postnatal depression and anxiety 61 . Thus, it is important to consider the socioeconomic and interpersonal influences on the intergenerational transmission of ACEs to children’s behavioural problems.…”
Section: Introductionmentioning
confidence: 99%